High-performance thermoelectric silver selenide thin films cation exchanged from a copper selenide template. Issue 1 (9th December 2019) - Chen, Nan; Scimeca, Michael R.; Paul, Shlok J.; Hafiz, Shihab B.; Yang, Ze; Liu, Xiangyu; Yang, Fan; Ko, Dong-Kyun; Sahu, Ayaskanta
Abstract : A high-performance n-type thermoelectric Ag2 Se thin film via cation exchange using a low-cost solution processed Cu2 Se template. Abstract : Over the past decade, Ag2 Se has attracted increasing attention due to its potentially excellent thermoelectric (TE) performance as an n-type semiconductor. It has been considered a promising alternative to Bi–Te alloys and other commonly used yet toxic and/or expensive TE materials. To optimize the TE performance of Ag2 Se, recent research has focused on fabricating nanosized Ag2 Se. However, synthesizing Ag2 Se nanoparticles involves energy-intensive and time-consuming techniques with poor yield of final product. In this work, we report a low-cost, solution-processed approach that enables the formation of Ag2 Se thin films from Cu2− x Se template films via cation exchange at room temperature. Our simple two-step method involves fabricating Cu2− x Se thin films by the thiol-amine dissolution of bulk Cu2 Se, followed by soaking Cu2− x Se films in AgNO3 solution and annealing to form Ag2 Se. We report an average power factor (PF) of 617 ± 82 μW m −1 K −2 and a corresponding ZT value of 0.35 at room temperature. We obtained a maximum PF of 825 μW m −1 K −2 and a ZT value of 0.46 at room temperature for our best-performing Ag2 Se thin-film after soaking for 5 minutes. These high PFs have been achieved via full solution processing without hot-pressing.